Personalizando com algoritmos: projetos de design para criação de peças únicas - GRACIANO, Andréa Pennino (2017)
The objective of this research is to investigate the possibilities of using algorithms in design projects, creating unique or customized pieces. It highlights the implications of the use of this tool on the creation process, since the designer, to take advantage of the programming codes potentialities, starts to design observing concepts like: repetition, modules, parameters. It explores the application of metadesign as the project design strategy, shifting the focus from the product to its creation process. In this case, the designer develops an algorithm (program) that virtually already includes all possible outcomes for the final product. The generation of distinct yet similar pieces is achieved through the manipu- lation of the input parameters of this code and/or the inclusion of random variables in its structure. As a case study, five projects are analyzed: Written Images (single piece), Square (limited edition), Dot One (customization), Crafted Technology (exclusive collection) and Orbi (parameterized typography), which illustrate the concepts presented throu- ghout the work.